Social isolation and cardiovascular health in US adults - Kieu, Chi; Behforooz, Susan; Wong, Nathan Donald (Scripta Medica, 2020)
Background. The relation of social isolation (SI) to global cardiovascular health (CVH) is not clear. We examined the association of CVH metrics to SI within US adults. Methods. Using the US National Health and Nutrition Examination Survey, we examined the association of SI with American Heart Association’s Life’s Simple 7 (LS7) CVH components (smoking, body mass index, physical activity, total cholesterol, diet, blood pressure, fasting blood glucose). The sum of the components (scored 1 for poor, 2 for intermediate, and 3 for ideal) created a composite CVH score. Multiple logistic regression provided the odds of SI according to levels of the LS7 components adjusted for age, sex, and ethnicity. Results. We studied 3528 adults aged ³40 years. The mean age, sex, and ethnicity-adjusted composite CVH score was 14.1 vs. 14.6 in those with vs. without SI (p<0.01). Multiple logistic regression examined individual LS7 components in relation to SI and showed the adjusted odds for SI for those with ideal vs. poor smoking status to be 0.57 (0.38-0.85), ideal vs. poor physical activity 0.53 (0.37-0.76), and ideal vs. poor fasting glucose 0.65 (0.47-0.91). Conclusion. Our study overall shows lower levels of CVH in those with vs. without SI, with nonsmoking status, ideal physical activity and ideal glucose levels were all less likely associated with SI, suggesting the potential value for screening for SI in identifying those at potential cardiovascular disease risk.